2018
DOI: 10.1158/1535-7163.mct-17-1185
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FDA-Approved Oncology Drugs with Selective Potency in High-Risk Childhood Ependymoma

Abstract: Children with ependymoma (EPN) are cured in less than 50% of cases, with little improvement in outcome over the last several decades. Chemotherapy has not affected survival in EPN, due in part to a lack of preclinical models that has precluded comprehensive drug testing. We recently developed two human EPN cell lines harboring high-risk phenotypes which provided us with an opportunity to execute translational studies. EPN and other pediatric brain tumor cell lines were subject to a large-scale comparative drug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Utilizing single-cell transcriptomic approaches we could further define undifferentiated subpopulations and differentiation trajectories within EPN tumor tissues [22,23]. In these previous studies, we identified fibroblast growth factor receptor 1 and 3 (FGFR1 and FGFR3) as potential therapeutic targets for EPN [11,23,35]. The mammalian fibroblast growth factor (FGF) family comprises 18 secreted proteins that interact with four different tyrosine kinase FGF receptors (FGFRs) [14].…”
Section: Extended Author Information Available On the Last Page Of The Articlementioning
confidence: 99%
“…Utilizing single-cell transcriptomic approaches we could further define undifferentiated subpopulations and differentiation trajectories within EPN tumor tissues [22,23]. In these previous studies, we identified fibroblast growth factor receptor 1 and 3 (FGFR1 and FGFR3) as potential therapeutic targets for EPN [11,23,35]. The mammalian fibroblast growth factor (FGF) family comprises 18 secreted proteins that interact with four different tyrosine kinase FGF receptors (FGFRs) [14].…”
Section: Extended Author Information Available On the Last Page Of The Articlementioning
confidence: 99%
“…In preclinical ependymoma assays, axitinib, imatinib, and pazopanib have shown promising results [ 99 ], so they may soon jump into clinical trials.…”
Section: Antiangiogenics and Brain Tumorsmentioning
confidence: 99%
“…Interestingly, a number of the identified compounds have also been identified in previous in vitro compound screens on smaller sets of glial tumors. 4145 Several of the compounds identified in our screen have also been tested in clinical trials for glioma in the past (see table S5), but none of the compounds were tested specifically in IDH-mutant patients. The current developments in local or enhanced CNS delivery methods opens up new treatment possibilities for highly potent compounds that do not have favorable characteristics to pass the BBB, such as romidepsin and dactinomycin.…”
Section: Discussionmentioning
confidence: 99%